2015
DOI: 10.1002/ajhb.22783
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth influences the timing of first menstruation

Abstract: The present data suggest that the season of birth influences sexual maturation rate in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…9,10,[21][22][23][24] One recent study among 1,697 Polish women found that those who were born during summer months (June to August) reported an average age at menarche that was 0.1, 0.3 and 0.2 years earlier than did women born during fall, winter and spring, respectively (P < 0.01). 9 In another study among 950 women from the United States, those born in February had an average age at menarche that was 0.5 years earlier than the menarche of women born in December (P < 0.04). 10 This difference was only statistically significant when the analyses were restricted to women born before 1970.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,[21][22][23][24] One recent study among 1,697 Polish women found that those who were born during summer months (June to August) reported an average age at menarche that was 0.1, 0.3 and 0.2 years earlier than did women born during fall, winter and spring, respectively (P < 0.01). 9 In another study among 950 women from the United States, those born in February had an average age at menarche that was 0.5 years earlier than the menarche of women born in December (P < 0.04). 10 This difference was only statistically significant when the analyses were restricted to women born before 1970.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the seasonal incidence of respiratory infections could be more marked at higher elevations. 9 It is also plausible that cooler overall temperatures at high altitudes are correlated with greater differences in seasonal behavior among pregnant women, which could affect exposure to sunlight (e.g. through clothing choices).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have noticed that age at menarche can be associated with the season of birth, or more accurately with seasonal differences in temperature, humidity, sunlight, rainfall, affecting the fetus in utero (Dossus et al, ; Kersemaekers et al, ; Kliś et al, ). The state of Madhya Pradesh is influenced by a sub‐tropical climate with a hot‐dry summer (April‐June) followed by the monsoon season (June‐September).…”
Section: Discussionmentioning
confidence: 99%
“…In the Northern hemisphere, previous research suggested that menarche peaks in winter or summer as compared with autumn and spring . We leave the investigation on the relationship between month and season at birth and age at menarche, which was also studied in the context of the Northern hemisphere, to future research. On the other hand, compared with other studies that asked adult women to retrospectively recall their age at menarche, often many years later, we anticipate that recall bias for menarcheal age in our data should be relatively lower, given the relatively short time span between the occurrence of menarche and the interview date.…”
Section: Discussionmentioning
confidence: 99%